Role of Employee Training: Study of Employee Commitment, Retention, and Performance in NADRA Pakistan - Umer Pathan, Samina; Salih Memon, Muhammad; Ahmed Soomro, Mansoor (International Journal of Psychosocial Rehabilitation, 2020)
Employee “commitment, retention, and performance" are the burning and debatable issues of every manufactured and service-oriented organization. In this prospective study, data has been collected from NADRA employees in Pakistan with the concern of training. A structured questionnaire was adopted and sent for data collection to the targeted population. Analysis techniques, namely descriptive statistics, reliability, factor analysis, regression, and correlation, were used, and based on the results, it was concluded that untrained employees are more committed, retain for long periods of time with NADRA, and perform better towards the organizational objective. On the other hand, employees who availed of training facilities are less committed, their retention rate is lower, and they do not perform well in the organization. It is finally concluded that only training factors without any financial and non-financial benefits are not effective on NADRA employees.